Faktor-Faktor Yang Mempengaruhi Penawaran Bibit Bawang Merah Jenis Bima Kulit Tipis Di Desa Tonjong Kecamatan Kramatwatu - Aliudin Aliudin; Aris Supriyo Wibowo; Meutia Meutia; Setiawan Sariyoga; Septian T C (JURNAL AGRIBISNIS TERPADU, 2019)
Seedlings, their offering behavior is different from other commodity seeds. This is due to the shelf life of shallot seeds which are very short and volumeous. These two things cause different behaviors, namely in abundant seasons the price of seed shallots is lower than in the rare harvest season. This behavior has limited the ability of farmers to be able to access shallots seeds. This study aims to analyze the factors that influence onion seed supply. This research is focused on the type of Bima Thin Skin onion. The study was conducted in Tonjong Village, Kramatwatu District, Serang Regency. Determination of the location is done purposively with sampling techniques done by Simple Random Sampling. Data analysis technique used is multiple linear regression. This study aims to analyze the factors that influence the supply of seed shallots, including: seed prices, NPK prices, TSP prices, and insecticide costs. The number of samples selected 54 of a total population of 155 people. Sample The results showed that there was a positive influence between the price of TSP fertilizer, Fungicide Costs, Insecticide Costs, on the amount of onion production offered, and there was a negative relationship between the price of onion seeds, NPK fertilizer price on the amount of production offered.